2000
DOI: 10.1002/1529-0131(200010)13:5<255::aid-anr3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about perceived functional disabilities and pain of people with rheumatoid arthritis: Differences between patients and their spouses and correlates with well-being

Abstract: Objective. In this study we examined the differences in perceptions of the patient's health status between rheumatoid arthritis (RA) patients and their spouses, and correlates of these differences with pa-tients' and spouses' well-being. Methods. A sample of 188 couples with one member receiving treatment for RA were selected from the rheumatology clinics in Twente, The Netherlands. The mean age of both RA patients and spouses was 56 years. Respondents completed questionnaires, including estimations of both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 26 publications
4
68
0
Order By: Relevance
“…Miaskowski, Zimmer, Barrett, Dibble, and Wallhagen [88] found that when caregivers had lower levels of pain assessment accuracy, patients had more mood disturbance and poorer quality of life. Riemsma, Taal, and Rasker [89] similarly found that both over-and underestimation of pain by partners was related to patients' poorer mental health status. Treating patients' pain requires the provider to perceive the cues to pain, interpret those cues to make an accurate assessment of the subjective experience of that pain and then respond accordingly [82].…”
Section: Practice Implicationsmentioning
confidence: 92%
“…Miaskowski, Zimmer, Barrett, Dibble, and Wallhagen [88] found that when caregivers had lower levels of pain assessment accuracy, patients had more mood disturbance and poorer quality of life. Riemsma, Taal, and Rasker [89] similarly found that both over-and underestimation of pain by partners was related to patients' poorer mental health status. Treating patients' pain requires the provider to perceive the cues to pain, interpret those cues to make an accurate assessment of the subjective experience of that pain and then respond accordingly [82].…”
Section: Practice Implicationsmentioning
confidence: 92%
“…Empathy might also account for why spouses often underestimate and overestimate pain and disability in ICPs. 13,16,24,66 Issues discussed and avoided during interactions might be just as important. One study showed that although most patients with chronic pain verbally communicated with their families about pain, they found it inappropriate to talk about the pain unless asked.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…14 Positive social support has been associated with better QOL in patients with RA in some cross-sectional studies, 19 whereas problematic social interactions, criticism, and/or a lack of social support is associated with poorer QOL. 20,21 Higher satisfaction with emotional support independently predicted improved QOL in RA patients, 22 though this buffering effect appeared to decrease over time. 23 Much of the prior research has focused on samples from Anglo-Saxon cultures and the importance of psychosocial factors (including depressive symptoms, anxiety, other psychopathology, and social support) on QOL in Latin Americans with RA has been less studied.…”
Section: Introductionmentioning
confidence: 99%